KUALITAS ASSURANCE STATEMENT ATAS SUSTAINABILITY REPORTS - Akhmad Ardi; Carmel Meiden (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The background is Sustainability report is one of the things that has attracted the attention of stakeholders recently because it is able to image company performance from three dimensions, namely the economic dimension, the environmental dimension, and the social dimension. The report is accompanied by an assurance statement by a globally recognized body or professional. Assurance statement or assurance engagement is a condition where a practitioner provides a conclusion on an information, which is designed to increase the trust of external information users. This study aims to determine the quality of state assurance in the sustainability report of companies in Indonesia. Using agency theory, legitimacy theory, stakeholder theory, assurance statement and ISAE 3000 & AA1000AS. The object of this study is a company listed on the Indonesia Stock Exchange (IDX) participants and winners of the Asia Sustainabilty Report Rating (ASRRAT) for the 2017-2021 period which publishes a complete and sequential sustainability report. The research design used is a descriptive study. The results of the analysis show that the quality of assurance statements in Indonesia, assurance statements issued by assurance providers for winning companies and participants of the Asia Sustainability Report Rating (ASRRAT) for the 2017-2021 period and the quality of assurance statements issued by assurance providers.